PENGARUH LATIHAN MENGGUNAKAN ALAT BANTU HAND PADDLE DENGAN PULL BOUY TERHADAP KECEPATAN BERENANG ATLET PUTRI 100 METER GAYA BEBAS - Yudha Triyantoro, - (2020)
The goal research to known practice influence using hand paddle with pull bouy about outcome swimming speed athlete women's 100 meters free swim. The population in this research are women athlete 11 until 14 years old, because less experienced acceleration in swimming 100 meters freestyle. The sample in this research are 10 person. The method is used experiment about consideration is that the reseacrh experiment to tried practice programe to known influence or result from treatment. In the research as factor will be tried is practice using hand paddle with pull bouy. The result of reseacrh proved is that there are practice influence using hand paddle with pull bouy. The advice from reseacher are for coaches or instructures swimming is so that applied practice methode using hand paddle with pull bouy free swim. Correlated did the writer should be held further reseach with different from this research. For swimmers that research outcome used as referenced one of the practice swimming.